Analysis of whey protein hydrolysates: peptide profile and ACE inhibitory activity - Marialice Pinto Coelho Silvestre; Mauro Ramalho Silva; Viviane Dias Medeiros Silva; Mariana Wanessa Santana de Souza; Carlos de Oliveira Lopes Junior; Wendel de Oliveira Afonso (Universidade de São Paulo, 2012)
The aim of this study was to prepare enzymatic hydrolysates from whey protein concentrate with a nutritionally adequate peptide profile and the ability to inhibit angiotensin-converting enzyme (ACE) activity. The effects of the type of enzyme used (pancreatin or papain), the enzyme:substrate ratio (E:S ratio=0.5:100, 1:100, 2:100 and 3:100) and the use of ultrafiltration (UF) were investigated. The fractionation of peptides was performed by size-exclusion-HPLC, and the quantification of the components of the chromatographic fractions was carried out by a rapid Corrected Fraction Area method. The ACE inhibitory activity (ACE-IA) was determined by Reverse Phase-HPLC. All parameters tested affected both the peptide profile and the ACE-IA. The best peptide profile was achieved for the hydrolysates obtained with papain, whereas pancreatin was more advantageous in terms of ACE-IA. The beneficial effect of using a lower E:S ratio on the peptide profile and ACE-IA was observed for both enzymes depending on the conditions used to prepare the hydrolysates. The beneficial effect of not using UF on the peptide profile was observed in some cases for pancreatin and papain. However, the absence of UF yielded greater ACE-IA only when using papain. O objetivo deste estudo foi preparar hidrolisados enzimáticos do concentrado proteico do soro de leite com perfil peptídico nutricionalmente adequado e com capacidade para inibir a atividade da enzima conversora da angiotensina (ECA). Os efeitos do tipo de enzima usado (pancreatina ou papaína), da relação enzima:substrato (E:S=0,5:100, 1:100, 2:100 e 3:100) e do uso da ultrafiltração (UF) foram investigados. O fracionamento dos peptídeos foi feito por CLAE de exclusão molecular e a quantificação dos componentes das frações cromatográficas foi realizada pelo método da Área Corrigida da Fração. A atividade inibitória da ECA (AI-ECA) foi determinada por CLAE de fase reversa. Todos os parâmetros testados afetaram tanto o perfil peptídico quanto a AI-ECA. O melhor perfil peptídico foi atingido para os hidrolisados obtidos com papaína, enquanto a pancreatina foi mais vantajosa em termos da AI-ECA. O efeito benéfico do uso de menor relação E:S sobre o perfil peptídico e a AI-ECA foi observado para ambas as enzimas dependendo das condições usadas para o preparo dos hidrolisados. O efeito benéfico da ausência da UF sobre o perfil peptídico foi observado em alguns casos para pancreatina e papaína. No entanto, a ausência da UF produziu maior AI-ECA somente quando a papaína foi usada.